2008
DOI: 10.4049/jimmunol.181.9.6010
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Size of the Alloreactive NK Cell Repertoire: Studies in Individuals Homozygous for the Group A KIR Haplotype

Abstract: Stem cell transplantation across HLA barriers may trigger NK cell-mediated graft-vs-leukemia effects leading to improved survival for patients with hematological malignancies. However, the genetic algorithm based on killer cell Ig-like receptor (KIR) and HLA genes used to predict NK cell alloreactivity have yielded discrepant results. Accordingly, it has been difficult to define transplantation settings that favor NK cell alloreactivity. In this study, we have used multiparameter flow cytometry to simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
114
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 65 publications
8
114
0
Order By: Relevance
“…Therefore, the selection of optimal donors is based, at the molecular level, on the analysis of donor KIR gene profile and of donor and recipient HLA class I typing. Importantly, recent data have demonstrated that, using combinations of different anti-KIR mAb, it is possible to define the size of the alloreactive NK cell subset (14,(36)(37)(38)(39)(40). Our present data indicate that the evaluation of the pool size of alloreactive NK cells in HSCT can only be possible by the use of appropriate mAb combination.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Therefore, the selection of optimal donors is based, at the molecular level, on the analysis of donor KIR gene profile and of donor and recipient HLA class I typing. Importantly, recent data have demonstrated that, using combinations of different anti-KIR mAb, it is possible to define the size of the alloreactive NK cell subset (14,(36)(37)(38)(39)(40). Our present data indicate that the evaluation of the pool size of alloreactive NK cells in HSCT can only be possible by the use of appropriate mAb combination.…”
Section: Discussionmentioning
confidence: 56%
“…The presence of alloreactive NK cells can be predicted by the analysis of the donor KIR gene profile and by the HLA class I typing of both donor and recipient. The actual presence and size of the alloreactive NK subset can be assessed by cytofluorimetric analysis using appropriate combinations of anti-KIR mAb (14,(36)(37)(38)(39)(40). In these experiments, alloreactive NK cells are identified as a subset expressing iKIRs specific for the mismatched KIR ligand but missing all the other iKIRs and NKG2A.…”
mentioning
confidence: 99%
“…During NK cell development, interactions between C1, C2, and Bw4 and cognate KIR determine the strength with which mature NK cells respond to cells whose HLA class I expression is perturbed by disease, a developmental process termed NK cell education (22). The A3/A11 epitope contributes little to NK cell education (23,24), a distinction that correlates with the exceptionally high sensitivity of KIR3DL2 to the peptide bound by HLA-A*03 or A*11 (21).…”
Section: Resultsmentioning
confidence: 99%
“…Functional education of human NK cells by HLA class I is well established (13,15,(39)(40)(41)(42), and a quantitative influence of HLA on NK cell responsiveness may explain, for example, how a single nucleotide polymorphism associated with a higher HLA-C expression levels is beneficial in acute HIV infection (43,44). The role of HLA class I molecules on the human NK cell repertoire is less clear, but is implied from studies showing that specific compound genotypes of KIR and HLA may provide protection or susceptibility to infections, cancers, and successful pregnancy (45).…”
Section: Discussionmentioning
confidence: 99%